Computational Modeling, Docking, Synthesis, Characterization, and in vitro Cyclooxygenase Inhibitory Activity of Some Novel Non-Steroidal Anti-inflammatory Prodrugs - Dana Muhammad Hamad Ameen; Sara Ramzi Abdulhameed (Zanco Journal of Pure and Applied Sciences, 2020)
Non-steroidal anti-inflammatory drugs (NSAIDs) are among the most prescribed analgesic and anti-inflammatory drugs. However, inhibition of cyclooxygenase1 and acidic groups such as carboxylic groups in most NSAIDs cause gastrointestinal (GI) side effects. Therefore, masking the acidic groups till it pass through the GI tract will decrease the direct GI side effects and because N-(2,6-dimethylphenyl)-acetamide 1 also has anti-inflammatory activity so the synthesized ester prodrugs might act as mutual prodrugs. 2-Chloro-N-(2,6-dimethylphenyl)-acetamide 1 was utilized to synthesize ester prodrug of various NSAIDs 2a-e. The 2-Chloro-N-(2,6-dimethylphenyl)-acetamide 1 undergo substitution reaction at α position with various sodium carboxylate of NSAIDs 2a-e in DMSO. The constitution of the newly synthesized ester prodrugs of NSAIDs 3a-e had been confirmed depending on their IR, ¹H and ¹³C-NMR spectral analysis. The synthesized ester prodrugs 3a-e were screened for their in vitro inhibitory activities of COX-1 as well as COX-2 however, their COX inhibition activity increased compared with their starting 1 and 2a-e. Physicochemical properties and “Lipinski’s rule of five” were assessed for compounds 3a-e, and they all satisfied the rule. Furthermore molecular docking for compounds 3a-e into COX-1 and COX-2 was done, in which they showed binding free energies ΔGb in the range of (-8.9 to -9.8 kcal/mol) when docked into COX-1 and (-10.4 to -12.4 kcal/mol) into COX-2 enzymes.